2018
DOI: 10.1017/s1368980018002458
|View full text |Cite
|
Sign up to set email alerts
|

Agreement of body adiposity index (BAI) and paediatric body adiposity index (BAIp) in determining body fat in Brazilian children and adolescents

Abstract: ObjectiveTo evaluate agreement of the body adiposity index (BAI) and paediatric body adiposity index (BAIp) in estimating body fat compared with dual-energy X-ray absorptiometry (DXA) and to propose cut-off points for these indices to classify excess adiposity in Brazilian children and adolescents.DesignCross-sectional study. Measures of weight, height, hip circumference, BMI and body fat percentage (%BF) assessed by DXA were taken, and BAI and BAIp were calculated. The Bland–Altman plot was used to estimate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
1
8
0
3
Order By: Relevance
“…However, this study used skinfold measurements as a reference method to validate the model, which is a limitation in studies of this nature. Other studies have observed a high proportion of bias and low agreement between the %BF predicted by DXA and the %BF predicted by BAI in Brazilian children and adolescents [15,16].…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…However, this study used skinfold measurements as a reference method to validate the model, which is a limitation in studies of this nature. Other studies have observed a high proportion of bias and low agreement between the %BF predicted by DXA and the %BF predicted by BAI in Brazilian children and adolescents [15,16].…”
Section: Introductionmentioning
confidence: 82%
“…A positive point of the present study was the establishment of objective criteria to validate the analyzed equations. Previously published studies have also carried out similar statistical analyses [11,15,29]. However, they have not clearly defined the validity criteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Naukowcy zamiennie stosują BAI i BAIp do oceny zawartości tkanki tłuszczowej u dzieci. Po przebadaniu 1049 osób w wieku od 8 do 19 lat wykazano, że Pediatric Body Adiposity Index wykazał niską zgodność z zawartością tkanki tłuszczowej obliczonej za pomocą DXA [65]. Autorzy wykazali, że BAI przeszacował procentową zawartość tkanki tłuszczowej średnio o 2,64% w porównaniu do wartości uzyskanych za pomocą DXA, natomiast BAIp zaniżył o 3,37%.…”
Section: Wskaźnik Otłuszczenia Ciała Pediatryczny -Baip (Pediatric Body Adiposity Index)unclassified